2014
DOI: 10.1016/j.semerg.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Documento de consenso para la detección y manejo de la enfermedad renal crónica

Abstract: Chronic kidney disease (CKD) is an important global health problem, involving to 10% of the Spanish population, promoting high morbidity and mortality for the patient and an elevate consumption of the total health resources for the National Health System. This is a summary of an executive consensus document of ten scientific societies involved in the care of the renal patient, that actualizes the consensus document published in 2007. The central extended document can be consulted in the web page of each societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
1
4
0
6
Order By: Relevance
“…Chronic kidney disease (CKD) is a major public health problem that has received increasing attention because of its association with the high rate of end stage renal disease (ESRD) (Eknoyan et al 2004 ; Liu et al 2015 ; Martinez-Castelao et al 2014 ). Proteinuria is often observed in patients with CKD, and it is reportedly a vital risk factor for the progression and prognosis of CKD (Sandsmark et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a major public health problem that has received increasing attention because of its association with the high rate of end stage renal disease (ESRD) (Eknoyan et al 2004 ; Liu et al 2015 ; Martinez-Castelao et al 2014 ). Proteinuria is often observed in patients with CKD, and it is reportedly a vital risk factor for the progression and prognosis of CKD (Sandsmark et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although cardiologists and endocrinologists evaluated in our study require periodic laboratory tests for hypertensive and diabetic patients, it is still necessary to include albuminuria and GFR exams in their routines. Other studies carried out in Senegal (13), Spain (14) and the United States (15) show that hypertension and DM are the main diseases that pose a risk of developing kidney damage, and that these diseases require preventive screening through laboratory tests, not only in adults but also in children in order to avoid developing CKD (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines recommend that in order to maintain good cardiovascular health and quality of life, every adult should perform physical exercise three to five times a week, with 30 minutes of light to moderate physical activity (18). In the case of established kidney disease, Martinez-Castelao et al reported that exercise should be adapted to the individual's physical capacity (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several wake-up calls should alarm diabetic patients regarding their kidneys' health, and patients should be referred to a nephrologist earlier if they present rapid renal reduction, resistant hypertension, hyperkalemia, UACR exceeding 300 mg/g, or other urinary abnormalities [56].…”
Section: Management Of Diabetes Mellitus In the Transition From Dkd To Esrdmentioning
confidence: 99%